2015
DOI: 10.1167/iovs.14-16341
|View full text |Cite
|
Sign up to set email alerts
|

How Many Visual Fields Are Required to Precisely Predict Future Test Results in Glaucoma Patients When Using Different Trend Analyses?

Abstract: Approximately 10 VFs, are needed to achieve an accurate prediction of PW VF sensitivity and mean sensitivity. Prediction error of PW VF sensitivity can be significantly minimized using the M-estimator robust regression model compared with conventional OLSLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 32 publications
7
58
1
Order By: Relevance
“…Reliable VFs were identified and eyes with at least eight reliable VFs were investigated, excluding the first VF measurement. We chose a minimum of eight VFs because it has recently been reported that this number is needed to precisely analyze VF progression2930313233. Eyes that experienced any surgical procedure, including trabeculectomy and cataract surgery, during or prior to this VF series period were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Reliable VFs were identified and eyes with at least eight reliable VFs were investigated, excluding the first VF measurement. We chose a minimum of eight VFs because it has recently been reported that this number is needed to precisely analyze VF progression2930313233. Eyes that experienced any surgical procedure, including trabeculectomy and cataract surgery, during or prior to this VF series period were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Thirteen eyes of 10 patients who had undergone cataract surgery before the baseline VF were included. We chose a minimum of 10 VFs because it has recently been reported that this volume is needed to precisely analyse VF progression 8. Systemic complications of hypertension (HT), migraine, family history of glaucoma (FH; second-degree blood relative) and smoking status were collected from medical records; all patients who had a note (positive or negative) on all these variables were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the method appears not to be significantly affected by the level of IOP or progression rate. However, despite a significant reduction in prediction error, the magnitude of this improvement is small relative to previous novel regression models that use only VF data345678910. One of the possible reasons for such a small improvement is that IOP fluctuates in the short and long term21 and measuring IOP at the clinic in approximately three month intervals is too infrequent to observe the true trend in IOP.…”
Section: Discussionmentioning
confidence: 92%
“…This is likely because VF progression is related to IOP level as suggested by numerous previous studies34. Various methods have been proposed to measure VF progression in glaucoma patients3479111213143536, however, simple time trend analysis remains the standard in clinical settings. Hence we compared the prediction performance of the IOP integrated trend analysis against the standard approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation